Penerapan Sistem Penilaian E-Kinerja dalam Perspektif Indeks Kepuasan Masyarakat pada Kantor Imigrasi Kelas I Non TPI Karawang - Dwi Rahmadia Putri; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Employee performance assessment serves as a crucial tool in gauging individual effectiveness and contribution, while also providing feedback and development strategies to enhance future performance and productivity. The Karawang Immigration Office has implemented an e-performance appraisal system that takes into account the public satisfaction index. This system incorporates data from public satisfaction surveys, employee performance data, and regulatory data as inputs. The assessment process utilizes a scoring method tailored to the employee's performance indicators. This research aims to explore the e-performance appraisal system at the Karawang Immigration Office from the public satisfaction perspective. Employing a qualitative descriptive approach, the study utilizes three data collection methods: interviews, observations, and document studies. The findings indicate that the implementation of the e-performance appraisal system based on the public satisfaction index at the Karawang Immigration Office has been successful. The system encourages improved employee performance and public satisfaction with the Karawang Immigration Office.